Features of representation of Island Text in Tove Jansson’s story «The Summer Book» - Перинець, Катерина (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Features of representation of Island Text in Tove Jansson’s story «The Summer Book» studied in this article. Based on the work on the study and description of Local Texts, the phenomenon of Island Text is considered as supertext whole, the symbolic manifestation of the island, reflected in the work of the Finnish writer. The mythologeme of paradise, the motives of life/death, birth/wilting, growing up/aging and the specific «island mentality» of the heroes are highlighted as constitutional features of Island Text of the story.It was found out that correlation of the image of paradise with the image of the island actualizes the mythologeme of paradise, which is central for the work and unites the motives of Island Text of the story. Exploration of this sacred paradise space leads to the regularization of the life of the islanders and their harmonious coexistence. On the other hand, the mythologeme of paradise, which is traditional for island literature, can be interpreted in a different way – childhood spent on the island-home become real paradise.The motives of life/death, birth/wilting, growing up/aging are the main motives of Island Text of «The Summer Book», they are literally embodied in the images of a girl and a grandmother; nature in summer and nature in autumn. Thus, the mythological chronotope is realized, characterized by cyclicality and reproducibility.It is shown that the «island mentality» of the heroes is determined by the concept of ours/stranger. The islanders obey their laws and reject the «others» who do not accept their ambivalent attitude. The topos of the sea is the natural border on the way to the island, associated with cosmogonic (water is a life) and with eschatological (water can bring a death) motives.